Metaphors of Mind : An Eighteenth-Century Dictionary - Pasanek, Brad, 1974- (Book collections on Project MUSE., 2015)
Brad Pasanek's unusual work is the written report of a massive digital humanities project that involved searching 18th-century texts for the many ways writers use metaphors to characterize the mind. The book takes a selection of broad metaphorical categories that the author discovered in his digital research - including animals, coinage, metal, rooms, and writing - and examines particular examples within each category. Pasanek also frames the "dictionary" elements of the project with a more theoretical discussion of what he calls "desultory reading," a form of "unsystematic perusal" of writing exemplified in the way we approach dictionaries. Pasanek not only argues that 18th-century thinkers largely employed desultory reading, but also that his work on this very project is itself an instance of this approach. The project succeeds twofold: in treating 18th-century writing as its topic and in exemplifying its approach. Pasanek maintains an accompanying website (https://metaphorized.com) that collects the results of his digital searches.